Pemberdayaan Kewirausahaan Anak Panti Asuhan Nur Fauzi melalui Pengembangan Produk UMKM Keripik Pangsit dan Gelang Manik-Manik serta Strategi Digital Marketing - M. Dimas Adi Fadhillah; Dr. Giriati S.E,. ME.; Destyana Fauziah Utami; Tio Rivaldi; Nabila Azka Salsabila; Dhiya 'Ulhaq Thursina (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The Student Community Service Program (KKM) aims to enhance the independence and creativity of children at the Nur Fauzi Orphanage in Pontianak through the development of entrepreneurship based on small and medium-sized enterprises (SMEs) and the utilization of digital marketing. The program is implemented through training in the production of citrus leaf chips and beaded bracelets as flagship products, and equipping participants with digital promotion skills through social media and design apps like Canva. Additionally, basic financial literacy education is provided creatively through activities such as making piggy banks from recycled bottles and casual discussions about the importance of saving. The approach combines educational, participatory, and practical methods, ensuring that children not only understand the theory but also gain real-world experience in entrepreneurship. The results of the activities show an increase in creativity, a spirit of independence, and basic skills in digital marketing of products. This program is expected to serve as a sustainable social empowerment model for other orphanages.